2019
DOI: 10.1186/s42269-019-0241-4
|View full text |Cite
|
Sign up to set email alerts
|

Mango (Mangifera indica) seed kernels as untraditional source of energy in Rahmani sheep rations

Abstract: Background: The present work aimed to investigate the impact of partial replacement yellow corn by mango seed kernels (MSK) at different levels of (0, 25, and 50%) on feed and water consumption, water metabolism, nutrient digestibility, nitrogen balance, and rumen fluid parameters. Methods: Twelve mature male Rahmani sheep of about 58.39 ± 1.22 kg live body weight on average were used to investigate the influence of replacing yellow corn contents (45% in the control ration) by mango seed kernels (MSK) at diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 18 publications
(21 reference statements)
5
9
0
Order By: Relevance
“…Similar to previous reports, the highest concentration of CF was for CFM3 (40% MS), while the lowest concentration was for CFM1 (0% MS), which may be due to the high CF in MS compared with corn gain ( 14 ). The present study also found that replacing corn with MS led to an increase in EE (2.94 to 3.30 g/100 g DM) and CF (11.17 to 13.59 g/100 g DM) in the tested feed mixtures, whereas the nitrogen-free extract content decreased from 60.63 to 58.04 g/100 g DM.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to previous reports, the highest concentration of CF was for CFM3 (40% MS), while the lowest concentration was for CFM1 (0% MS), which may be due to the high CF in MS compared with corn gain ( 14 ). The present study also found that replacing corn with MS led to an increase in EE (2.94 to 3.30 g/100 g DM) and CF (11.17 to 13.59 g/100 g DM) in the tested feed mixtures, whereas the nitrogen-free extract content decreased from 60.63 to 58.04 g/100 g DM.…”
Section: Resultssupporting
confidence: 88%
“…The OM, CP, EE, and ash contents were nearly similar for the different diets, whereas CF tended to increase and NFE decrease with increasing MS levels. In line with other research, MS was shown to have greater concentrations of growth energy and CF, because the kernel is usually a significant source of fat, starch, and protein ( 7 , 14 ). Similarly, it was reported that mango kernels included a higher percentage of fat, starch, and protein ( 34 , 35 ).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…However, MSK can be used to replace up to 50% of yellow corn grains in the sheep rations without any adverse effect on their feed intake, digestion coefficients, and ruminal fermentation. Consequently, MSK which is not competing and nonconventional feedstuff for animals was found useful as an economic replacement for energy materials like yellow corn grains (Omer et al, 2019). Replacement of the corn grains (33%) by MSM was recommend by Silva et al (2016), because of the better fermentation of fiber carbohydrates and reduces feeding costs.…”
Section: Discussionmentioning
confidence: 99%